ACETYLSALICYLIC ACID IN THE PREVENTION OF ATHEROTHROMBOTIC EVENTS - A. V. Govorin; A. P. Filev (Столичная издательская компания, 2015)
The results of large-scale clinical trials have convincingly demonstrated the effectiveness of acetylsalicylic acid (ASA) in primary and secondary prevention of atherothrombotic events. Studies on the safety of different ASA formulations have been continuing. Magnesium hydroxide included in combined medicine, Сardiomagnil, prevents ASA adverse effects on the gastric mucosa and reduces in severity of dyspeptic symptoms.